Limited Mouth Opening Secondary to Diffuse Systemic Sclerosis - Tomoko Wada; Saravanan Ram (Case Reports in Dentistry)
Systemic sclerosis (SSc) is a relatively rare condition with an immunologically mediated pathogenesis. For reasons that are not clearly understood, dense collagen is deposited in the connective tissues of the body in extraordinary amounts. Although its dramatic effects are seen in association with the skin, the disease is often quite serious with visceral organ involvement. We describe a case of limited mouth opening secondary to diffuse SSc, improvement in mouth opening with passive jaw stretch exercises, and the challenges involved in performing dental procedures for such patients.